1985
DOI: 10.1109/edl.1985.26129
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-shallow high-concentration boron profiles for CMOS processing

Abstract: The fabrication of ultra-shallow high-concentration boron profiles in silicon has been carried out utilizing a XeCl excimer laser. The Gas Immersion Laser Doping (GILD) process relies on a dopant species, in this case diborane (BIHs), to be adsorbed on the clean silicon surface and subsequently driven in during a melthegrowth process initiated upon exposure to the short laser pulse. Secondary Ion Mass Spectrometry and spreading resistance profiles show peak boron concentrations from 5 X 1019 to 5 X 1O'O depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Each sample was irradiated with ten spatially homogenized laser pulses at an energy of 0.35 J/cm . The process relies on the pulsed excimer laser radiation to rapidly heat and melt the silicon surface [14]. Talwar demonstrated that the laser processing does not degrade the gate oxide integrity [15].…”
Section: Methodsmentioning
confidence: 99%
“…Each sample was irradiated with ten spatially homogenized laser pulses at an energy of 0.35 J/cm . The process relies on the pulsed excimer laser radiation to rapidly heat and melt the silicon surface [14]. Talwar demonstrated that the laser processing does not degrade the gate oxide integrity [15].…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13][14] Typically, implants have been activated, but defects and changes in surface stoichiometry are reported. [10][11][12] Recent reports 13,14 using excimer laser activation of ion implanted dopants is promising, although the potential to incorporate dopants from the gas phase without ion implantation, as has been demonstrated in silicon, [15][16][17] has not been reported to date.…”
Section: ͓S0003-6951͑99͒04022-x͔mentioning
confidence: 99%
“…Carey et al [6] reported the Gas Immersion Laser Doping (GILD) process where Si wafer is irradiated by laser light in B 2 H 6 gas ambient. Sameshima et al [7] reported the Laser-Induced Melting of Predeposited Impurity Doping (LIMPID) technique, where a Si wafer with deposited dopant film is irradiated by a pulsed laser light.…”
Section: Introductionmentioning
confidence: 99%